Respon Gedung Portal Baja Akibat Pembesaran Gempa Oleh Lapisan Tanah: Steel Frame Response Subject To Seismic Amplification By Soil Deposit - Kori Effendi, Mahmud; Susilawati, Herlina; Diana, Nur Ayu; Artha, F. Dona (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Yogyakarta city is one of the earthquake prone areas in Indonesia that has historical buildings, high-rise buildings, road structures and bridges. The soil profile affects the amplification from bedrock to the ground surface. The bedrock acceleration is taken from the matched design response spectrum SNI by means SeismoMatch. The output of the NERA software shows that the ground acceleration is increasing from 0,249 g to 0,385 g or about 1,5 times compared to bedrock. The SAP2000v14 is used as dynamic analysis software. The modal analysis result that the 7 modes are enough for the analysis, so that it meets the mass participation ratio requirements in article 7.9.1 SNI-1726-2012 which is ≥ 90%. The results of dynamic earthquake analysis by both Time History and Response Spectrum analysis have relatively the same results in displacement, axial force and bending moment. In the Modal Time History 1 (MHIST 1) the large time interval affects the bending moment. After the small-time interval is used, both Modal Time History 2 (MHIST 2) and Direct Integration Time History (DHIST 2) give the same results.